2018
DOI: 10.1002/dc.24069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of using lubricant during the speculum examination for Pap smear collection

Abstract: Objective To evaluate the effect of using lubricant during speculum examination for Pap smear collection. Methods A cross‐sectional study was conducted involving 83 patients attending a medical school clinic. Participants were allocated into two groups: Group 1—Lubricant using; Group 2—No lubricant using. All patients were submitted to two successive collections and after were asked about their level of discomfort. Differences between groups regarding quality, artifacts, cytology, and level of discomfort were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In Brazil, Nunes et al 4 performed a double-blind randomized clinical trial between August 2012 and June 2013, with the objective of evaluating the effect of the use of lubricating gel in the speculum during cervicovaginal cytology examination. It included 83 women aged between 15 and 44 years, randomly divided into two groups: group 1 (cervicovaginal cytology was first performed with a dry speculum and later with a small amount of liquid petroleum jelly) and group 2 (both cervicovaginal cytology exams were performed with a dry speculum).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Brazil, Nunes et al 4 performed a double-blind randomized clinical trial between August 2012 and June 2013, with the objective of evaluating the effect of the use of lubricating gel in the speculum during cervicovaginal cytology examination. It included 83 women aged between 15 and 44 years, randomly divided into two groups: group 1 (cervicovaginal cytology was first performed with a dry speculum and later with a small amount of liquid petroleum jelly) and group 2 (both cervicovaginal cytology exams were performed with a dry speculum).…”
Section: Resultsmentioning
confidence: 99%
“… 2 As for Hill et al and Nunes et al's RCTs, they included only women of childbearing age and concluded that the use of lubricating gel decreases the pain felt, without altering the CVC result. 3 4 Finally, the metanalysis by Pergialiotis et al concluded that the use of aqueous lubricant on the speculum does not interfere with the result of conventional CCV nor does it significantly alleviate the discomfort felt.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations